2004
DOI: 10.3406/morfo.2004.1219
|View full text |Cite
|
Sign up to set email alerts
|

L'évolution des falaises argilo-crayeuses et limoneuses du nord du Boulonnais (Strouanne, Sangatte, France) / Evolution of the clay-chalk and silt cliffs in northern Boulonnais (Strouanne, Sangatte, France)

Abstract: L'évolution des falaises argilo-crayeuses et limoneuses du nord du Boulonnais (Strouanne, Sangatte, France) / Evolution of the clay-chalk and silt cliffs in northern Boulonnais (Strouanne,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 17 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…At Folkestone Warren (UK), Hutchinson (1969) demonstrated that there is no relationship between the majority of the groundwater in the Gault slipped masses and that of the inland chalk aquifer. Actually, variation of the liquid limit in the Gault and mass movements at Strouanne (Figure 2(C)) are the result of the infiltration of rain water on the cliff face where the Gault outcrops (Pierre and Lahousse, 2004). Groundwater action on weakly cemented clastics (Norris, 1990) is well illustrated by the processes observed in the bedded deposits of the Sangatte cliff.…”
Section: Resultsmentioning
confidence: 85%
“…At Folkestone Warren (UK), Hutchinson (1969) demonstrated that there is no relationship between the majority of the groundwater in the Gault slipped masses and that of the inland chalk aquifer. Actually, variation of the liquid limit in the Gault and mass movements at Strouanne (Figure 2(C)) are the result of the infiltration of rain water on the cliff face where the Gault outcrops (Pierre and Lahousse, 2004). Groundwater action on weakly cemented clastics (Norris, 1990) is well illustrated by the processes observed in the bedded deposits of the Sangatte cliff.…”
Section: Resultsmentioning
confidence: 85%